Novel technique of removal of broken intra-medullary nail from femur with secondary DCS plating - Mahajan, Neetin Pralhad; Pande, Kartik Prashant; Bagimani, Pramod K. (International Journal of Research in Orthopaedics, 2021)
Femoral shaft fractures are one of the commonest fractures of the lower limb which are frequently operated with intramedullary nailing which enables immediate post-operative mobilization of the patient. There could be various causes of nail breakage – some of the notable being weight bearing over the non-union of the femur shaft, or a re-trauma over the operated limb causing both the implant and the nail to be broken. There are various methods of removal of the broken implant the commonest being the use of T-reamer technique. However not always can this be used due to varied intra-operative obstacles in different cases as described in this case below. We have a 35 year old male patient who was brought to us 2 hours after an alleged history of slip and fall following which he had sustained right sided subtrochanteric femur fracture with a broken implant – intramedullary interlock nail. The patient is a previously operated case of right sided femur shaft fracture with interlocking nailing done 15 years back. The patient was operated with – broken implant removal on the right side along with a secondary DCS plating with bone grafting for the subtrochanteric femur fracture. Intra operative period was met with a certain number of challenges and difficulties in view of a 15 year old implant for removal which was successfully with removed with DCS plating done. As is obvious with the above case, it would be quite imperative to say that older the implant, more difficult it becomes for its removal.